1998
DOI: 10.1161/01.cir.98.25.2873
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Fontan Pathway Flow Dynamics by Multidimensional Phase-Velocity Magnetic Resonance Imaging

Abstract: Background-Hemodynamic efficiency of Fontan circulation is believed to be a major determinant of outcome. Prior research on flow dynamics in different modifications of Fontan circulation used in vitro models and computer-based simulation. This study was designed to compare in vivo flow dynamics in the systemic venous pathway between patients with atriopulmonary anastomosis (APA) and those with total cavopulmonary connection (TCPC). Methods and Results-Multidimensional phase-velocity magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 21 publications
(21 reference statements)
0
49
0
Order By: Relevance
“…It was de Leval's landmark in vitro experimental work that first demon strated energy conservation in the TCPC as opposed to the atriopulmonary connection [6]. Subsequently, an in vivo magnetic resonance imaging study has also demon strated improved flow dynamics in the TCPC over the atriopulmonary connection [9]. In a recent study, compu tational modeling of different types of TCPC demon strated that offsetting of the caval connection was efficient [13].…”
Section: Flow At Connection Sitementioning
confidence: 99%
“…It was de Leval's landmark in vitro experimental work that first demon strated energy conservation in the TCPC as opposed to the atriopulmonary connection [6]. Subsequently, an in vivo magnetic resonance imaging study has also demon strated improved flow dynamics in the TCPC over the atriopulmonary connection [9]. In a recent study, compu tational modeling of different types of TCPC demon strated that offsetting of the caval connection was efficient [13].…”
Section: Flow At Connection Sitementioning
confidence: 99%
“…Magnetic resonance (MR) phase velocity mapping (PVM) [22] is currently the only established clinical technique to measure all three spatial components of the velocity vector in every volume element of an imaging slice, showing high in vitro and in vivo accuracy and precision [23][24][25][26][27][28][29][30][31][32][33][34]. The advantage of MR PVM to measure the three-directional blood velocity has enabled the generation of velocity vector maps in vitro and in vivo, showing (qualitatively) the fluid mechanical superiority of the TCPC over other connections and the importance of the presence of caval offset and flaring at the connection site [14,15,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…during diastasis. Using multidimensional phase contrast CMR imaging, Be'eri et al 72 demonstrated that blood flow patterns are more organized and uniform in lateral tunnel than in atriopulmonary Fontan pathways and are significantly influenced by pathway diameter. CMR has been shown to be more accurate than lung scintigraphy in quantifying blood flow to each lung in the Fontan circulation.…”
Section: Evaluation Of the Functionally Single Ventriclementioning
confidence: 99%